2004
DOI: 10.1016/j.orthres.2003.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional kinematics of the glenohumeral joint during simulated simple translation tests: Impact on clinical diagnoses

Abstract: At the end ranges of motion, the glenohumeral capsule limits translation of the humeral head in multiple directions. Since the 6-degree of freedom kinematics of clinical tests are commonly utilized to diagnose shoulder injuries, the objective of this study was to determine the magnitude and repeatability of glenohumeral joint kinematics during a simulated simple anteroposterior translation test in the anterior and posterior directions. A magnetic tracking system was used to determine the kinematics of the hume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…1,5,12,29 In our study, anterior loading yielded translations of about 5 mm after capsulotomy, compared with a range from 9 to 18 mm reported by Moore et al 29 for an intact shoulder. However, we applied a small translation force of 25 N, which is similar to the translation force used by Harryman et al 12 (30 N), but considerably smaller than the forces applied by Moore et al 29 (simple translation test: maximum manual loading) and Burkart et al 5 (50 N).…”
Section: Discussionsupporting
confidence: 47%
“…1,5,12,29 In our study, anterior loading yielded translations of about 5 mm after capsulotomy, compared with a range from 9 to 18 mm reported by Moore et al 29 for an intact shoulder. However, we applied a small translation force of 25 N, which is similar to the translation force used by Harryman et al 12 (30 N), but considerably smaller than the forces applied by Moore et al 29 (simple translation test: maximum manual loading) and Burkart et al 5 (50 N).…”
Section: Discussionsupporting
confidence: 47%
“…In other words, a clinician may not have to position the contralateral shoulder in the exact same position as the injured shoulder while performing the test. Although encouraging in improvement of a quantitative translation test of the shoulder, prior biomechanical studies [9,10,20] had led us to hypothesize that translations of the shoulder in the abduction and external rotation position would be less than those in the abducted and neutral rotation position that were tested previously. Moore et al [20] used a magnetic motion tracking system to assess AP glenohumeral translations in cadaveric shoulders during a simulated simple translation test.…”
Section: Discussionmentioning
confidence: 98%
“…Although encouraging in improvement of a quantitative translation test of the shoulder, prior biomechanical studies [9,10,20] had led us to hypothesize that translations of the shoulder in the abduction and external rotation position would be less than those in the abducted and neutral rotation position that were tested previously. Moore et al [20] used a magnetic motion tracking system to assess AP glenohumeral translations in cadaveric shoulders during a simulated simple translation test. They found that anterior translation decreased with the abducted shoulder positioned in 30°of external rotation compared with neutral rotation and also decreased at 60°of external rotation.…”
Section: Discussionmentioning
confidence: 98%
“…A clinician translated the humeral head to its limit in the anterior direction at 01, 301, and 601 of external rotation (ER) and 601 of abduction while joint kinematics were recorded. The reproducibility of this loading method and the accuracy of the measurements have been published previously (Moore et al, 2004b). Accuracy of the magnetic sensors is o0.3% of the distance between the sensors and o1.01 (Moore et al, 2004b;Zeminski, 2001).…”
Section: Experimental Kinematicsmentioning
confidence: 93%
“…The reproducibility of this loading method and the accuracy of the measurements have been published previously (Moore et al, 2004b). Accuracy of the magnetic sensors is o0.3% of the distance between the sensors and o1.01 (Moore et al, 2004b;Zeminski, 2001).…”
Section: Experimental Kinematicsmentioning
confidence: 93%